Accounting Contribution to the Effectiveness of Tourism Destination Management - ARTINI, Gusti Ayu Kade Dwika Budi; PRADNYADEWI, Gusti Ayu Putu Indah; LAKSANA, I Putu Satya Dharma; CAHYANA, I Putu Edik Artha; PUTRA, Dudek Febriana (Journal Management and Hospitality, 2024)
This study aims to analyze the contribution of accounting to the effectiveness of tourism destination management in Bali. The study explains how the application of good accounting principles can improve financial management efficiency, resource control, and performance evaluation of tourism destinations. The study's results demonstrate that accounting plays a vital role in providing accurate financial information, thereby supporting more informed and transparent decision-making for destination managers. Furthermore, the implementation of an effective accounting system enables managers to plan budgets, control expenses, and optimize revenue more accurately. Thus, accounting not only improves management effectiveness but also supports the sustainability and competitiveness of tourism destinations in Bali. In addition, the study emphasizes the importance of capacity building for accounting human resources, as well as the integration of digital technologies to enhance reporting accuracy, efficiency, and stakeholder trust in the tourism sector. Continuous improvement and regular evaluation are also needed to adapt to dynamic challenges.